Tomato spotted wilt virus benefits a non-vector arthropod, Tetranychus urticae, by modulating different plant responses in tomato - Nachappa, Punya; Margolies, David C.; Nechols, James R.; Whitfield, Anna E.; Rotenberg, Dorith (My University, 2013)
The interaction between plant viruses and non-vector arthropod herbivores is poorly understood. However, there is accumulating evidence that plant viruses can impact fitness of non-vector herbivores. In this study, we used oligonucleotide microarrays, phytohormone, and total free amino acid analyses to characterize the molecular mechanisms underlying the interaction between Tomato spotted wilt virus (TSWV) and a non-vector arthropod, twospotted spider mite (Tetranychus urticae), on tomato plants, Solanum lycopersicum. Twospotted spider mites showed increased preference for and fecundity on TSWV-infected plants compared to mock-inoculated plants. Transcriptome profiles of TSWV-infected plants indicated significant up-regulation of salicylic acid (SA)-related genes, but no apparent down-regulation of jasmonic acid (JA)-related genes which could potentially confer induced resistance against TSM. This suggests that there was no antagonistic crosstalk between the signaling pathways to influence the interaction between TSWV and spider mites. In fact, SA- and JA-related genes were up-regulated when plants were challenged with both TSWV and the herbivore. TSWV infection resulted in down-regulation of cell wall-related genes and photosynthesis-associated genes, which may contribute to host plant susceptibility. There was a three-fold increase in total free amino acid content in virus-infected plants compared to mock-inoculated plants. Total free amino acid content is critical for arthropod nutrition and may, in part, explain the apparent positive indirect effect of TSWV on spider mites. Taken together, these data suggest that the mechanism(s) of increased host suitability of TSWV-infected plants to non-vector herbivores is complex and likely involves several plant biochemical processes.
Citation: Nachappa P, Margolies DC, Nechols JR, Whitfield AE, Rotenberg D (2013) Tomato Spotted Wilt Virus Benefits a Non-Vector Arthropod, Tetranychus Urticae, by Modulating Different Plant Responses in Tomato. PLoS ONE 8(9): e75909. doi:10.1371/journal.pone.0075909
Keywords: Tomato spotted wilt virus; Twospotted spider mite; Tetranychus urticae; Tomato; Solanum lycopersicum